Biomass generation and biodiesel production from macroalgae grown in the irrigation canal wastewater - Kanda Whangchai; Vannasinh Souvannasouk; Prakash Bhuyar; Rameshprabu Ramaraj; Yuwalee Unpaprom (Water Science and Technology, 2021)
The wastewater concentration is commonly acceptable for macroalgae growth; this process consumes water and is applicable for bioremediation. This study evaluated biodiesel's potential production from freshwater macroalga, Nitella sp., using batch experiment. Algae were collected from wastewater saturated from irrigation canals. Water quality and algae growth environment characteristics were monitored and analyzed. COD and BOD values were 18.67 ± 4.62 mg/L and 5.40 ± 0.30 mg/L, respectively. The chemical composition contents were high, demonstrating that water quality and sufficient nutrients could support algae growth. Oil extraction was estimated by the room temperature and heat extraction methods. The biodiesel in room temperature treatment was 0.0383 ± 0.014%, and in heat, extraction treatment was 0.0723 ± 0.029%. Results confirmed that the heat extraction treatment gave a high amount of oil and biodiesel yield. Gas chromatography/mass spectrometry (GC/MS) was used to analyze fatty acid methyl esters (FAME). Results revealed that 9-octadecane was a major portion of the substance. The obtained results confirmed that the wastewater contains many elements that can be utilized for dual-mode, like bioremediation and enhanced macroalgae growth for biodiesel production. Therefore, macroalgae grown in canal wastewater were highly feasible for use in sustainable biodiesel production. HIGHLIGHTS Irrigation wastewater-grown algae were utilized.; Waste water contents can be utilized for dual mode bioremediation and energy generation.; Wastewater-grown algae content rich in nitrogen, and organic contents.; Reflux reaction gives enhanced biodiesel production.; Nitella sp. is viable for sustainable biodiesel production.;